Implementasi IMPLEMENTASI MICE EVENT DALAM PROGRAM IISMA-E DI FRANKFURT SCHOOL OF FINANCE AND MANAGEMENT - aura syaliha; Imam Syafganti; Christina L. Rudatin (Bisnis Event, 2026)
The Indonesian International Student Mobility Awards for Entrepreneurs (IISMA-E) program is an initiative by the Ministry of Education, Culture, Research, and Technology of the Republic of Indonesia aimed at providing international exposure for vocational students. This study aims to describe the implementation of MICE (Meeting, Incentive, Conference, Exhibition) activities carried out during the IISMA-E program at the Frankfurt School of Finance and Management, Germany. This research uses a qualitative descriptive method with data collected through direct observation and documentation. The results show that the application of MICE in this program provided students with practical experience in organizing international-scale events, expanding professional networks, and understanding global work culture. The two main events analyzed in this study were the Asia Berlin Summit and the Panel Discussion with the Consulate General of Indonesia in Frankfurt. Keyword: MICE, IISMA-E, international event, vocational students, global experience